1991
DOI: 10.1111/j.1600-0536.1991.tb01770.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transcutaneous penetration of nicotinates and sensitive skin

Abstract: Proclivity to develop irritant reactions and transcutaneous penetration of nicotinates has been investigated in 20 subjects of both sexes, divided into reactors and nonreactors on the basis of the responses to irritant stimuli. 1% sodium lauryl sulphate (patch application for 24 h) and 5% lactic acid in aqueous solutions were used to detect chemical and sensory (subjective) irritation. The vasodilatation induced was measured using a chromameter for 1 h after topical application of the chemical. The area-under-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 12 publications
(12 reference statements)
1
37
1
1
Order By: Relevance
“…The application of LA, SLS, capsaicin or cumene failed to enhance differences in erythema responses [20,50,51,53], while the application of octane, acetyl-b-methylcholine chloride, allergen patch testing (European standard and cosmetics), and methyl nicotinate resulted in a stronger erythema response in stingers and in sensitive skin [37,51]. Similar results on methyl nicotinate were found in 1991 [1]. Remarkably, 1 study observed a blanching reaction following methyl nicotinate solely in subjects with sensitive skin [37].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The application of LA, SLS, capsaicin or cumene failed to enhance differences in erythema responses [20,50,51,53], while the application of octane, acetyl-b-methylcholine chloride, allergen patch testing (European standard and cosmetics), and methyl nicotinate resulted in a stronger erythema response in stingers and in sensitive skin [37,51]. Similar results on methyl nicotinate were found in 1991 [1]. Remarkably, 1 study observed a blanching reaction following methyl nicotinate solely in subjects with sensitive skin [37].…”
Section: Resultssupporting
confidence: 63%
“…Various imprecisely defined terms have been proposed to characterize susceptible skin, emphasizing its heterogeneous presentation, and only few research groups have focused on objective approaches to identify differences in sensitive skin [1,2,3,4,5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…These observations impressively underline how differently the protection barrier and the penetration barrier may behave, an observation which had already been described in a different context [28]. Biophysical statements relating to the skin barrier should therefore be limited to statements concerning singular qualities – even though the behavior is often parallel [5, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…When chemical erythema was induced using an MEC of methyl nicotinate, greater reductions in erythema were seen in ibuprofen-treated sites compared with sites treat-vestigators typically administer a standard concentration of methyl nicotinate to all test subjects using concentrations between 36.5 and 100 m M to induce erythema [9][10][11][12][13][14] . However, previous reports indicate that there are individual differences in the extent of erythema response to methyl nicotinate [15] , suggesting that a standard concentration of methyl nicotinate for all test subjects may result in variable responses when evaluating topical anti-infl ammatories. In the current study, we determined that there is a range for the lowest concentration required to induce erythema.…”
Section: Introductionmentioning
confidence: 88%